2003
DOI: 10.1002/eji.200324406
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐induced autoantibody formation in mice: triggering by primed CD4+CD25 T cells, prevention by primed CD4+CD25+ T cells

Abstract: Although the ability of CD4 + CD25 + T suppressor (Ts) cells to prevent experimental autoimmune diseases has been described, nothing is known concerning their role and mechanism of action in xenobiotic-induced autoimmunity. Procainamide, mercuric chloride, and gold(I) are three xenobiotics that can induce autoimmune reactions in humans and rodents. After the induction of IgG1 antinuclear autoantibodies (ANA) in mice treated with either of the above xenobiotics, adoptive transfer of their CD4 + CD25 + T cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…Notably, our data showing significantly decreased percentages of CD4 + CD25 + T-cells in mice exposed to mercury in utero are consistent with proposed models suggesting that regulatory T-cells may play a role in susceptibility to metal-induced autoimmunity in rats (Kosuda et al, 1991). Further evidence supporting an immunoregulatory role for Tregs in mercury-induced autoimmunity has been derived from a study that found adoptive transfer of CD4 + CD25 + T-cell fractions into mercury-treated H-2 s mice effectively prevented the formation of anti-nuclear autoantibodies (ANA) (Layland et al, 2004). However, while there is substantial evidence to date supporting a significant role for immunoregulatory populations in modulating strain-specific responses to mercury-induced autoimmunity, it is likely that other factors such as genetic susceptibility and cytokine secretion profile may influence loss of tolerance mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…Notably, our data showing significantly decreased percentages of CD4 + CD25 + T-cells in mice exposed to mercury in utero are consistent with proposed models suggesting that regulatory T-cells may play a role in susceptibility to metal-induced autoimmunity in rats (Kosuda et al, 1991). Further evidence supporting an immunoregulatory role for Tregs in mercury-induced autoimmunity has been derived from a study that found adoptive transfer of CD4 + CD25 + T-cell fractions into mercury-treated H-2 s mice effectively prevented the formation of anti-nuclear autoantibodies (ANA) (Layland et al, 2004). However, while there is substantial evidence to date supporting a significant role for immunoregulatory populations in modulating strain-specific responses to mercury-induced autoimmunity, it is likely that other factors such as genetic susceptibility and cytokine secretion profile may influence loss of tolerance mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…+ T-cell fractions abrogated the formation of anti-nuclear antibodies in mercury-treated H-2 s mice (Layland et al, 2004). These findings and the results of our study suggest that prenatal mercury exposure may have long-lasting inhibitory effects on regulatory networks that could possibly enhance autoimmunity.…”
Section: Discussionsupporting
confidence: 74%
“…Evidence supporting this hypothesis comes from a very interesting study that has investigated the role of CD4 + CD25 + and CD4 + CD25 À T cells in drug-induced autoantibody formation after exposure to procainamide, mercury chloride and gold [44 ]. Layland et al [44 ] found that adoptive transfer of CD4 + CD25 + T cells obtained from mice treated with either of the above xenobiotics completely prevented the formation of ANAs in recipient mice treated with the same xenobiotic.…”
Section: Drug Metabolism Can Cause Antigenic Modification Of Self-commentioning
confidence: 98%